On Separate Names of Objects of Telšiai District - Mickienė, Ilona (Respectus Philologicus, 2001)
The word-building of one toponymic class in one particular region is being discussed for the first time in the works of Lithuanian toponymy. While analysing the toponyms of Telšiai District, a number of names were left aside as they denoted the location rather than the names of various objects and therefore did not suit to any toponymic class. Not all the names of single objects discussed in the article can be treated as proper names of locality.The analysis is based on 639 known examples. Having analysed the names of the single objects in Telšiai District it was observed that the uttermost part of them is composed of secondary names. The group of the secondary names fixed is almost 30 times larger than that of the primary names.
Keywords: toponymy; the name of single objects; word-building (formation); semantic groups